2015
DOI: 10.1055/s-0035-1545204
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vancomycin-resistant Enterococcus faecium and E. faecalis activities of (-)-gossypol and derivatives from Thespesia garckeana

Abstract: Authors may reproduce/republish portions of their published contribution without seeking permission from NPC, provided that any such republication is accompanied by an acknowledgment (original citation)-Reproduced by permission of Natural Product Communications. Any unauthorized reproduction, transmission or storage may result in either civil or criminal liability. The publication of each of the articles contained herein is protected by copyright. Except as allowed under national "fair use" laws, copying is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Compound 22 was isolated from Mentha pulegium and exhibited moderate activity with an IC 50 value of 8.5 μg/mL ( Ibrahim, 2013 ). The dimeric sesquiterpenoid gossypol ( 23 ), which is also known from the cotton plant, was isolated from Thespesia garckeana by Masila et al (2015) and showed an IC 50 of 4.66 μg/mL. Häkkinen et al (2021) tested the germacranolide lactones parthenolide ( 24 , from Tanacetum parthenium ) and lactucopicrin ( 25 , from Cichorium intybus ) against a β-lactamase possessing strain, with pronounced effects (MIC value of 0.16 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 22 was isolated from Mentha pulegium and exhibited moderate activity with an IC 50 value of 8.5 μg/mL ( Ibrahim, 2013 ). The dimeric sesquiterpenoid gossypol ( 23 ), which is also known from the cotton plant, was isolated from Thespesia garckeana by Masila et al (2015) and showed an IC 50 of 4.66 μg/mL. Häkkinen et al (2021) tested the germacranolide lactones parthenolide ( 24 , from Tanacetum parthenium ) and lactucopicrin ( 25 , from Cichorium intybus ) against a β-lactamase possessing strain, with pronounced effects (MIC value of 0.16 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…While 82 was only moderately active (with a MIC value of 31.25 μg/mL), the methylated form (83) showed pronounced effects (MIC: 7.81 μg/mL). Zuo et al (2015) isolated two biphenyl compounds, 84 and 85, from Biancaea sappan, which was previously ascribed to the genus Caesalpinia, in a bioactivity-guided isolation procedure. Both compounds showed moderate to low activity but demonstrated synergistic effects in combination with amikacin and gentamycin (Figure 5).…”
Section: Caffeic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used traditionally to enhance libido as its consumption is traditionally claimed to enhance development of a strong desire for sexual intercourse in both males and females alike, suggesting its possible aphrodisiac property. Azanza garckeana has been reported to possess antibacterial and antifungal activities [2][3][4][5], anti-hyperglycemic effect [6], antioxidant and cytotoxicity activity [5,7] and antimalarial property [8]. Some of these pharmacological properties have been attributed to some of the phytochemicals such as tannins, flavonoids, saponins, alkaloids and xanthones that are found in it [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Azanza garckeana has been reported to possess antibacterial and antifungal activities [2][3][4][5], anti-hyperglycemic effect [6], antioxidant and cytotoxicity activity [5,7] and antimalarial property [8]. Some of these pharmacological properties have been attributed to some of the phytochemicals such as tannins, flavonoids, saponins, alkaloids and xanthones that are found in it [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%